Mathematical Communication Ability across Learning Styles: A Systematic Review and a Differentiated Instructional Framework - Charis Maulana; Alim Jaizul (Research Collaboration Community (Rescollacom), 2026)
Mathematical communication is one of the core competencies students need in order to interpret, represent, and justify mathematical ideas, yet Indonesian students' performance on international literacy assessments such as the Programme for International Student Assessment (PISA) has remained persistently below the international average. Prior research has repeatedly linked this gap to students' learning styles – visual, auditory, and kinesthetic – but existing reviews mostly stop at describing which style performs comparatively better, without translating the findings into concrete instructional guidance and without accounting for the growing use of technology-integrated mathematics instruction. This study addresses that gap through a systematic literature review of empirical studies published between 2017 and 2025, retrieved from Google Scholar and SINTA-accredited Indonesian journal databases using the keywords